PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN BADAN USAHA MILIK DESA (BUMDesa) DI KABUPATEN MANGGARAI TIMUR - Mayolus A. Chorvinno Tatu; Sarinah J. M Rafael (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
ABSTRACT In the era of government now the village plays an important role where the village is the front guard to identify any problems that exist in society. One way for the village to prosper the community is to establish a Village-Owned Enterprise (BUMDesa). This study aims to determine whether there is an influence of the accounting information system on the performance of BUMDesa employees / administrators in East Manggarai Regency. This research uses a mix method. This research was conducted at 12 BUMDesa in East Manggarai Regency. The results of this study indicate that the accounting information system has a positive effect on employee / management performance in East Manggarai Regency. The magnitude of the influence of the accounting information system on performance is 29.8%. The results of the interviews also showed the same results where from the elaboration of each indicator the researchers concluded that the accounting information system affected the performance of BUMDesa employees/administrators in East Manggarai Regency. Keywords: Accounting Information System, Performance of Employees, Village Owned Enterprises